Relações de gênero e poder: a vivência de mulheres e homens sob o impacto da migração internacional. - - Amorim, Aparecida [UNESP] (2015)
Contemporary society has been widely marked by transnational relations. As technology has advanced and globalization has become predominant, migration trends have expanded, blurring national borders between countries. Therefore, one can now observe not only a rapid dissemination of commercial and intellectual transactions, but also a substantial increase of people seeking better economic and social opportunities. In order to do this, they travel to countries that project a standard of living above their own. However, these individuals, after leaving their native land - by themselves or with their families - continue to maintain strong bonds with their places of origin, leaving them in an ever fluctuating state of subjectivity, in which they no longer identify as citizens of their home country or as citizens of the new. Within such processes, many scholars have noted the formation of social networks - clandestine or not - that are aimed at facilitating international exchanges of people. (MASSEY, 1990 e 2006; TILLY, 1990; SOARES, 2003; ASSIS, 2011, SIQEIRA, 2009). This work intends to investigate the way in which these subjects renegotiate their marriages and kinship in terms of class, gender, and ethnicity. My focus is the well-known migratory route between Governador Valadares, in Minas Gerais, and the metropolitan area of Boston, Massachusetts, in the United States. I interviewed couples who have already returned, who are still in the US, as well as those who, because of the dislocation, got divorced. Throughout these narratives, I attempted to focus on the changes in the dynamics of gender and power, which these experiences had imposed. Furthermore, this study emphasized the crucial role of women in the articulation of these movements. The theoretical apparatus used in this investigation included works by Appadurai (2000), Eriksen (2006) e Brah (2006), in the Cultural Studies Field, as well as reflections by Butler (2008), Moore...